Your own business : a practical guide to success - Reynolds, Wal, 1942-; Williams, Alan.; Savage, Warwick (Melbourne : Nelson, 1994)
This book is divided into four parts: Background; Thinking; Starting; Succeding; and Growing of your own bisiness.
Keywords: Management; Small business; Management; Small business -- Australia